Effect of heat stress on metabolic analysis of sweat in dairy cattle - Anítas, Özgül; Göncü, Serap; Hepsag, Fatma; Özogul, Yeşim (Revista de Ciências Agroveterinárias, 2025)
During heat stress, dairy cattle use a variety of physiological and cellular mechanisms to dissipate heat from their bodies and protect cells from damage. In this process, the change in the fatty acid content of the sweat released from animals contains important findings in terms of regulating body temperature. In this study, the maximum ambient temperature during the day varied between 35 °C and 37 °C, and the relative humidity varied between 37% and 49%. Fatty acid ratios of sweat samples taken from Holstein and Jersey cows under heat stress were determined by gas chromatography. Myristic acid (C14:0), palmitic acid (C16:0), stearic acid (C18:0) and oleic acid (C18:1n9c), fatty acids with the highest ratios in sweat, were recorded. These fatty acids were 9.28%, 26.24%, 11.43%, 26.39% in Holstein cow sweat, respectively; It was detected in Jersey cow sweat at the rates of 10.19%, 23.83%, 27.63%, 20.83%. Total monounsaturated fatty acid content in sweat of Holstein and jersey cows was determined as 26.39% and 20.83%, while total saturated fatty acid content was determined as 46.95% and 61.65%, respectively. The total percentage of fatty acids with the highest percentage detected in sweat under heat stress conditions (myristic acid, palmitic acid, stearic acid and oleic acid) was 73.34% in Holstein cows and 82.48% in Jersey cows. Apart from these, the percentage of other compounds detected in sweat constituted 26.66% in Holstein and 17.52% in Jersey cows. As a result of correlation analysis, a strong positive (r=757) and significant (P<0.01) relationship was found between sweat fatty acids and sweat fatty acids of Holstein and Jersey cows in summer months. It was determined that especially the stearic acid rates (11.43%, 27.63%) in the sweat of Holstein and Jersey. The low level of stearic acid in the sweat of Holstein cows indicates that stearic acid from fat tissue is not used much as an energy source. Jersey cows under heat stress were quite different. Based on these findings, stearic acid detected in the sweat of animals can be determined as a heat stress bioindicator. Differences in the fatty acid ratios in sweat in the study show that the two breeds exhibit different adaptation responses under the same conditions, at the same temperature and humidity.